Effect of Ultrasonic Assisted on The Degree of Deacetylation of Chitosan Extracted from Portunus Pelagicus - Buanasari, Buanasari; Sugiyo, Warlan; Rustaman, Heri (Universitas Negeri Semarang, 2021)
The technology for extracting chitin from shell and other materials needs to be continuously improved, including its conversion to chitosan. Chitosan is a biocompatible polymer, biodegradable, non-toxic, water-soluble at pH below 6.5, and it has protonated amino groups. The benefits of chitosan in industry, food and medicine make it necessary to fully study an efficient chitosan synthesis method and the results can be applied on an industrial scale. This study examined the effect of ultrasonic-assisted in increasing the degree of deacetylation of chitosan produced from Portunus pelagicus shell waste. The production process of chitosan goes through the stages of deproteination, demineralization and deacetylation. All these steps are ultrasound assisted processes with a frequency of 40 kHz through a digital ultrasonic cleaner. Ultrasonic-assisted chitin and chitosan were examined using FTIR spectrometry. The results showed that the ultrasonic method was able to increase the deacetylation degree of chitin with a value of 68.45±0.11% compared to 62.52±0.08% without ultrasonic. Application of ultrasonic assisted deacetylation gave a deacetylation degree of 85.35 ± 0.20%, higher than without ultrasonic 80.24 ± 0.19%. Physically, ultrasonic-assisted chitosan is smoother and brighter in color. The ultrasonic-assisted chitosan manufacturing method could increase the deacetylation degree and produce high grade chitosan.